Enhanced activation of peroxymonosulfate by nitrogen-doped graphene/TiO2 under photo-assistance for organic pollutants degradation: Insight into N doping mechanism. (April 2020) - Zhao, Ya; Wang, Guanlong; Li, Lujie; Dong, Xiaoli; Zhang, Xiufang
Abstract: Production of sulfate radical from peroxymonosulfate (PMS) activation by carbon-based catalysts is a promising strategy to degrade pollutants. However, the electron-transfer ability of carbon catalysts, which is critical in PMS activation, still needs to be improved. In this study, a novel photo-assisted PMS activation system (PPAS) was constructed on a nitrogen-doped graphene/TiO2 (NG/TiO2 ), in which the photogenerated electrons excited from TiO2 could be utilized by NG for enhanced PMS activation on it. Moreover, the N content was varied to firstly investigate the role of N doping on PPAS. Under photo-assistance, the NG/TiO2 displayed significantly enhanced PMS activation for removal of organic pollutants. 100% bisphenol A (BPA) can be removed within 1 h. The results show that the degradation kinetic constant of BPA by the NG/TiO2 PPAS was 24 times higher than that under PMS alone, and was 1.4 times higher than that of rGO/TiO2 PPAS. The singlet oxygen ( 1 O2 ) and sulfate radical (SO4 − ) were the main reactive species in PPAS. The outstanding performance of NG/TiO2 system was ascribed to the two main reasons: on one hand, the N doping decreased the schottky barrier formed between NG and TiO2, which favored the electron transfer from TiO2 to NG. On the other hand, the N doping enhanced the adsorption and electron-transfer ability of NG towards PMS. Graphical abstract: Image 1 Highlights: Peroxymonosulfate was activated on NG/TiO2 under photo-assistance for BPA removal. N doping level greatly influences the performance of catalytic system. Singlet oxygen and sulfate radical are the main reactive species. N doping reduces the schottky barrier between NG and TiO2 for electron transfer. N doping enhances the adsorption capacity of PMS on NG.